Proceedings of the Third Workshop on Vision and Language 2014
DOI: 10.3115/v1/w14-5408
|View full text |Cite
|
Sign up to set email alerts
|

Twitter User Gender Inference Using Combined Analysis of Text and Image Processing

Abstract: Profile inference of SNS users is valuable for marketing, target advertisement, and opinion polls. Several studies examining profile inference have been reported to date. Although information of various types is included in SNS, most such studies only use text information. It is expected that incorporating information of other types into text classifiers can provide more accurate profile inference. As described in this paper, we propose combined method of text processing and image processing to improve gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Ulges et al (2012) detected TV viewers' gender and age via content-based concept detection. Ikeda et al (2013) and Sakaki et al (2014) used methods that incorporate information. Ikeda et al (2013) proposed a hybrid-based method using both text and community membership.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Ulges et al (2012) detected TV viewers' gender and age via content-based concept detection. Ikeda et al (2013) and Sakaki et al (2014) used methods that incorporate information. Ikeda et al (2013) proposed a hybrid-based method using both text and community membership.…”
Section: Related Workmentioning
confidence: 99%
“…Ikeda et al (2013) proposed a hybrid-based method using both text and community membership. Sakaki et al (2014) proposed a hybrid-based method using a combination of text and images, which builds a meta-classifier using the probability score out- put from text and image classifiers as input. This study demonstrated that a combination of text and images boosts the accuracy of a single source.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations